Dynamic control of phase for tunable structural colors - Aritra Biswas; Mahdi Soudi; Souptik Mukherjee; Pablo Cencillo-Abad; Jay Patel; Debashis Chanda (Proceedings of the National Academy of Sciences, 2025)
Structural coloration offers many advantages over conventionally used pigment-based colors due to their nontoxic, fade-resistant, and environmentally friendly nature. These colors arise from the structural arrangements of colorless materials at the nanoscale, which create optical resonances and vibrant hues. Over the last decade, dynamic color generation has been the subject of extensive research across various scientific disciplines. However, commercial adoption has been limited by the absence of effective tuning mechanisms, structural complexities, and fabrication challenges. In this work, we demonstrate active color tuning based on phase modulation of a multilayer stack composed of a phase-changing material (PCM) and a high-index material on a reflective surface. We elucidate the underlying interfacial and cavity phase modulation mechanisms responsible for the dynamic color changes, highlighting the potential for tailoring the optical properties of this thin-film stack for a wide range of practical applications. Furthermore, we showcase the lithography-free implementation of this concept for large-area, color-tunable textiles, complex surfaces, and temperature-sensitive consumer product labeling, highlighting its efficacy in tunable, scalable, and sustainable coloration. Leveraging dynamic phase modulation, this concept holds immense promise for applications in thermal sensing, advanced textile engineering, camouflage, and reconfigurable displays.